LITERATURE REVIEW: EFFECTIVENESS OF HEALTH PROMOTION MEDIA ON THE LEVEL OF MATERNAL KNOWLEDGE ABOUT STUNTING - Yuliana, Putri; Astuti, Yuli; Leny Wulandari, Rr. Catur (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Stunting is a condition of malnutrition that occurs when a child's growth and development is disrupted due to chronic malnutrition, frequent infections, and/or inadequate psychosocial stimulation. This results in children being shorter than expected for their age, with long-term consequences for their physical and cognitive development, as well as their future health and economic prospects. Maternal knowledge about stunting is considered very important in the prevention and control of stunting in children. One of the influencing factors is maternal knowledge about stunting, so efforts need to be made to increase maternal knowledge through health promotion media. This Literature Review aims to collect and evaluate the latest literature related to the effectiveness of health promotion media on the level of maternal knowledge about stunting. The literature study was conducted using three scientific publication search engines, namely Pubmed and Google Scholar. From the search results, 13 articles were selected published between 201 9-2023 and can be accessed for free that health promotion media are considered to have good effectiveness in increasing maternal knowledge about stunting, media that can be used in providing health promotion about stunting are Leaflets, Booklets, Brochures, cards and Video while video media is considered more effective than other media in increasing maternal knowledge about stunting.